2008
DOI: 10.2147/vhrm.s2410
|View full text |Cite
|
Sign up to set email alerts
|

A young man with acute dilated cardiomyopathy associated with methylphenidate

Abstract: An 18-year-old obese man with a body mass index of 40, diagnosed with attention-defi cit hyperactivity disorder and treated with methylphenidate (Concerta ® ) was acutely admitted to hospital with hypoxia and dyspnoea. On investigation signs of liver-, renal-, and heart-failure were found. Noradrenalin infusion was started. Echocardiography showed dilated left ventricle and an ejection fraction (EF) of 25%. Liver function improved, noradrenalin and dobutamine were tapered, but three days after admission a new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
14
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 8 publications
(7 reference statements)
1
14
0
Order By: Relevance
“…He developed ST elevation in EKG that was normalized with 36 h. Then, the authors mentioned association of cardiomyopathy and pericarditis with methylphenidate. This association was supported by the reports of previous studies [2,3].…”
supporting
confidence: 91%
See 1 more Smart Citation
“…He developed ST elevation in EKG that was normalized with 36 h. Then, the authors mentioned association of cardiomyopathy and pericarditis with methylphenidate. This association was supported by the reports of previous studies [2,3].…”
supporting
confidence: 91%
“…The reference of Tollofsrud [3] was not in English and I could not study it. The second reference, the Nymark et al [2] reported a patient with body mass index of 40 who has taken quetiapine 900 mg/day for 17 months and methylphenidate was added. However, there is another report for possible association of cardiomyopathy and methamphetamine use in young patients [6].…”
mentioning
confidence: 99%
“…There are very few reports linking methylphenidate therapy to DCM. Two reports from Norway described serious cardiomyopathy in young patients treated with methylphenidate (20)(21). One of them was severly obese (BMI-40).…”
Section: Methylphenidate's Toxicitymentioning
confidence: 99%
“…Two recent cases from Norway described the development of dilated cardiomyopathy in young patients after years of methylphenidate use [5,6]. Treatment duration in one case was 1 year and in the other case 10 years [5,6]. To our knowledge, this is the first reported case of acute cardiomyopathy and myopericarditis associated with a single dose of methylphenidate.…”
mentioning
confidence: 90%
“…However, to date there have been very few case reports linking methylphenidate to cardiomyopathy and even fewer linking methylphenidate to pericarditis. Two recent cases from Norway described the development of dilated cardiomyopathy in young patients after years of methylphenidate use [5,6]. Treatment duration in one case was 1 year and in the other case 10 years [5,6].…”
mentioning
confidence: 99%